INTERNALISASI PROGRAM MARI BUANG SAMPAH PADA TEMPATNYA (MARBUNGSAMTEM) TERHADAP KARAKTER PEDULI LINGKUNGAN DI SDN TAMAN CIRUAS PERMAI - Kiki Rizky Amalia; Ujang Jamaludin; Encep Andriana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to see the internalization of “Mari Buang Sampah Pada Tempatnya” (Marbungsamtem) Program at SDN Taman Ciruas Permai. This research used a descriptive qualitative research method. Data were collected through interview, observation, and documentation. Interviews were conducted with the principal, teachers, and parents of students. Observations were made in two places, namely environment SDN Taman Ciruas Permai and the students’ housing environment of Taman Ciruas Permai. Meanwhile, the documentation was carried out at the time of pre-research and research. This documentation was done when the interview was finished at school as well as at students’ homes during the observation activities as well as doing research documentation. The results of this study indicated that: (1) the process of internalizing “Mari Buang Sampah Pada Tempatnya” (Marbungsamtem) Program to the character of environmental care was implemented in two stages, namely planning and implementation. (2) factors inhibiting and supporting the internalization of “Mari Buang Sampah Pada Tempatnya” (Marbungsamtem) Program to the character of environmental care came from the school environment and the home environment of students.